UJI KELAYAKAN BATU PECAH DESA PARIDA KECAMATAN LASALEPA KABUPATEN MUNA SEBAGAI AGREGAT KASAR CAMPURAN BETON - Irvan Jaya; Romy S. E. Tamburaka; Wayan Mustika (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2020)
Abstract In Muna Regency, there are some kinds of mountain rocks, including in Parida Village, Lasalepa District. There is a place where local people usually take crushed stone to be used as a material for making concrete. The area of land where the local people used to collect mountain stones was ± 2 hectares. Based on the description, the writer considers it necessary to conduct research in order to complete the final project by taking the title "Feasibility Test for Broken Stone Materials in Parida Village, Lasalepa District, Muna Regency as Coarse Aggregates in Concrete Mixtures" with the formulation of the problem of how coarse aggregate characteristics (crushed stone) ) from Parida Village, Lasalepa District, Muna Regency and what is the feasibility of coarse aggregate (crushed stone) from Parida Village, Lasalepa District, Muna Regency, for concrete mixtures with f'c 20 Mpa. The purpose of this study was to determine the characteristics of coarse aggregate (crushed stone) from Parida Village, Lasalepa District, Muna Regency and also to determine the feasibility of coarse aggregate (crushed stone) from Parida Village, Lasalepa District, Muna Regency, for concrete mixtures with f'c 20 Mpa.Based on laboratory tests, the results obtained moisture content 0.49%, 1.02% sludge content, 2,53 SSD specific gravity, 1,37 gram/cm3 volume weight, 1,95% absorption, 35,90% wear. The results of the concrete compressive strength test that has been carried out reach an average quality of 13,97 MPa at 7 days old, 16,26 MPa at 14 days old, and 21,04 Mpa at 28 days old. So the conclusion from the research that has been done is that the crushed stone of Parida Village, Lasalepa District, Muna Regency is declared suitable for use as coarse aggregate for concrete mixtures with f'c 20 Mpa quality.  Abstrak Di Kabapaten Muna banyak terdapat batu gunung, tidak terkecuali di Desa Parida kecamatan Lasalepa. Di daerah tersebut terdapat tempat dimana masyarakat setempat biasa mengambil batu pecah untuk digunakan sebagai bahan pembuatan beton. Luas lahan dimana para penduduk setempat biasa mengambil batu gunung adalah ± 2 hektare. Maka berdasarkan dari uraian di atas sehingga penulis memandang perlu untuk melakukan penelitian dalam rangka penyelesaian tugas akhir dengan mengambil judul ”Uji Kelayakan Material Batu Pecah Desa Parida Kecamatan Lasalepa Kabupaten Muna Sebagai Agregat Kasar Pada Campuran Beton” dengan rumusan masalah bagaimana karakteristik agregat kasar (batu pecah) asal Desa Parida Kecamatan Lasalepa Kabupaten Muna dan bagaimana kelayakan agregat kasar (batu pecah) asal Desa Parida Kecamatan Lasalepa Kabupaten Muna,  untuk campuran beton dengan f’c 20 Mpa. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik agregat kasar (batu pecah) asal Desa Parida Kecamatan Lasalepa Kabupaten Muna dan juga untuk mengetahui kelayakan agregat kasar (batu pecah) asal Desa Parida Kecamatan Lasalepa Kabupaten Muna, untuk campuran beton dengan f’c 20 Mpa.Berdasarkan pengujian laboratorium yang dilakukan, diperoleh hasil kadar air 0,49 %, kadar lumpur 1,02 %, berat jenis SSD 2,53, berat volume 1,37 gram/cm3, absorbtion 1,95 %, keausan 35,90%. Dan hasil dari pengujian kuat tekan beton yang telah dilakukan mencapai mutu rata-rata 13,97 Mpa diumur 7 hari, 16,26 Mpa diumur 14 hari, dan 21,04 Mpa diumur 28 hari. Maka kesimpulan dari penelitian yang telah dilakukan yaitu batu pecah Desa Parida Kecamatan Lasalepa Kabupaten Muna dinyatakan layak untuk digunakan sebagai agregat kasar untuk campuran beton dengan mutu f’c 20 Mpa.